Monoclonal antibody RYSK173 recognizes the dinuclear Zn center of serum carnosinase 1 (CN-1): possible consequences of Zn binding for CN-1 recognition by RYSK173 - Zhang, Shiqi; Lindner, Holger A.; Krämer, Bernhard; Yard, Benito A.; Hauske, Sibylle J. (PLOS ONE, 2016)
Background and Aims The proportion of serum carnosinase (CN-1) recognized by RYSK173 monoclonal antibody negatively correlates with CN-1 activity. We thus hypothesized that the epitope recognized by RYSK173 is accessible only in a catalytically incompetent conformation of the zinc dependent enzyme and we mapped its position in the CN-1 structure. Since patients with kidney failure are often deficient in zinc and other trace elements we also assessed the RYSK173 CN-1 proportion in serum of these patients and studied the influence of hemodialysis hereon in relation to Zn2+ and Cu2+ concentration during hemodialysis. Methods and Results Epitope mapping using myc-tagged CN-1 fragments and overlapping peptides revealed that the RYSK173 epitope directly contributes to the formation of the dinuclear Zn center in the catalytic domain of homodimeric CN-1. Binding of RYSK173 to CN-1 was however not influenced by addition of Zn2+ or Cu2+ to serum. In serum of healthy controls the proportion of CN-1 recognized by RYSK173 was significantly lower compared to end-stage renal disease (ESRD) patients (1.12 ± 0.17 vs. 1.56 ± 0.40% of total CN-1; p<0.001). During hemodialysis the relative proportion of RYSK173 CN-1 decreased in parallel with increased serum Zn2+ and Cu2+ concentrations after dialysis. Conclusions Our study clearly indicates that RYSK173 recognizes a sequence within the transition metal binding site of CN-1, thus supporting our hypothesis that metal binding to CN-1 masks the epitope. The CN-1 RYSK173 proportion appears overall increased in ESRD patients, yet it decreases during hemodialysis possibly as a consequence of a relative increase in transition metal bound enzyme.